COSTUMER SATISFACTION ANALYSIS OF RICE BRAN COFFEE PRODUCTS - Winda Amilia; Clara Septaria Melinda; Andrew Setiawan Rusdianto; Nita Kuswardhani; Miftahul Choiron (UNEJ e-Proceeding, 2022)
Legendaris Koka is a company that provides various kinds of coffee innovations, one of them is ricebran coffee is located on Jl. Letjen. Panjaitan No. 22 Jember Regency. Rice bran coffee is a coffee blended with rice bran after roasting process with the aim of creating a distinctive taste and aroma from the combination of coffee and rice bran. The purpose of this research is to determine the attributes of importance and the value of suitability of importance on performance and consumer satisfaction "Legendaris Koka" ricebran coffee product. Implementation of this research is analyzing data from consumer questionnaires ricebran coffee Legendary Koka using Importance Performance Analysis (IPA) methods to determine the value of suitability of importance in the performance and Customer Satisfaction Index (CSI) methods to determine the value of customer satisfaction. The method Importance Performance Analysis (IPA) shows that the main priority attributes to improve their performance are those in quadrant I, that is a taste attribute with a suitability value of 83.221%. The results of Customer Satisfaction Index (CSI) is 74.529% with the predicate satisfied. Keywords: Rice Bran Coffee, Healthy drink, Customer Satisfaction, marketing, Customer Satisfaction Index